Endosome traffic machinery meets the p53–p21 axis - Barroso-González, Jonathan (Mol Cell Oncol, 2014)
SIRT1 regulates p53 transcriptional activation in response to genotoxic insult by deacetylating key lysine residues. We recently identified the multifunctional protein PACS-2 as a SIRT1 inhibitor. After DNA damage, PACS-2 binds and inhibits SIRT1 to increase p53-dependent transactivation of the CDK inhibitor p21 (CDKN1A) and induce cell cycle arrest.